A STUDY ON ECG FINDINGS IN ACUTE LIVER CELL FAILURE DUE TO RAT KILLER PASTE POISONING - AL, SETHURAMAN; R, BALAMURALI; M, MANIMARAN; S, CHITRA; G, SATHYA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to study the various electrocardiogram (ECG) manifestations in patients who develop acute liver cell failure due to rat killer paste poisoning. Methods: Patients who developed acute liver cell failure due to rat killer paste ingestion admitted during the time period of July 2022–December 2022 in our institution were taken up for the study. Serial ECG monitoring was done in all these patients and observed for any changes. Results: Eighty-eight cases of rat killer paste poisoning that developed acute liver failure during this time period were included in the study. Out of 88 patients, 24 patients (27%) had ECG manifestations. The different ECG manifestations are ST depression with T wave inversion – 13 patients (10 expired), QT prolongation – 8 patients (3 expired), sinus bradycardia – 2 patients, and atrial fibrillation with rapid ventricular rate – 1 patient (expired). The mean time of onset of ECG findings is 22 h from intake of poison. The overall mortality rate is 23% (20 patients). About 70% of expired patients (14 patients) had abnormal ECG manifestations. Conclusion: ST depression with T wave inversion was the most common ECG manifestation due to rat killer paste poisoning in our study and it correlates with mortality. Since cardiotoxicity due to rat killer paste poisoning is also a major contributor to mortality, proper measures have to be taken to create awareness to the general public regarding the toxicity of rat killer paste.